Brain morphometry in transient global amnesia: a triangulated analysis approach - Micaela Anahi Hernández; Hernán Chaves; Ricardo Francisco Allegri; Ismael Luis Calandri (Dementia & Neuropsychologia)
ABSTRACT Transient global amnesia (TGA) is a rare, temporary, sudden-onset disturbance in anterograde episodic memory with unclear pathophysiology. Previous brain volumetric analysis in TGA patients showed varied results. Objective: To explore brain morphometry, hypothesizing that patients with TGA exhibit structural alterations. Methods: A case-control study was performed involving TGA subjects (n=50) and matched healthy controls (n=50). Both groups underwent a 3D-T1 weighted structural MRI on a 3T scanner, and voxel-based morphometry (VBM), region-based morphometry (RBM), and surface-based morphometry (SBM) were analyzed. Results: After performing the VBM, RBM, and SBM analyses, no consistent and statistically significant differences were found after applying multiple corrections. Conclusion: Despite previous studies showing volumetric changes in TGA patients, our results differ from this. The discrepancy could be due to sample size and timing of MRI scans. While our findings do not explain TGA pathophysiology, they support a network dysfunction as a possible mechanism and discards a structural alteration as a predisposing factor for TGA.